A novel reciprocal crosstalk between RNF168 and PARP1 to regulate DNA repair processes - Kim, Jae Jin; Lee, Seo Yun; Kim, Soyeon; Chung, Jee Min; Kwon, Mira; Yoon, Jung Hyun; Park, Sangwook; Hwang, Yiseul; Park, Dongsun; Lee, Jong Soo; Kang, Ho Chul (Molecules and Cells, 2018)
Emerging evidence has suggested that cellular crosstalk between RNF168 and poly(ADP-ribose) polymerase 1 (PARP1) contributes to the precise control of the DNA damage response (DDR). However, the direct and reciprocal functional link between them remains unclear. In this report, we identified that RNF168 ubiquitinates PARP1 via direct interaction and accelerates PARP1 degradation in the presence of poly (ADP-ribose) (PAR) chains, metabolites of activated PARP1. Through mass spectrometric analysis, we revealed that RNF168 ubiquitinated multiple lysine residues on PARP1 via K48-linked ubiquitin chain formation. Consistent with this, micro-irradiation-induced PARP1 accumulation at damaged chromatin was significantly increased by knockdown of endogenous RNF168. In addition, it was confirmed that abnormal changes of HR and HNEJ due to knockdown of RNF168 were restored by overexpression of WT RNF168 but not by reintroduction of mutants lacking E3 ligase activity or PAR binding ability. The comet assay also revealed that both PAR-binding and ubiquitin-conjugation activities are indispensable for the RNF168-mediated DNA repair process. Taken together, our results suggest that RNF168 acts as a counterpart of PARP1 in DDR and regulates the HR/NHEJ repair processes through the ubiquitination of PARP1.
Keywords: DNA Damage; DNA End-Joining Repair; DNA Repair; HEK293 Cells; HeLa Cells; Homologous Recombination; Humans; Mutagenesis, Site-Directed; Poly (ADP-Ribose) Polymerase-1; Signal Transduction; Ubiquitin-Protein Ligases; Ubiquitination; DNA repair; PARP1; Parylation; RNF168; Ubiquitination